Update of the parasitic crustacean holdings of the Museo de la Plata, Argentina - Diaz, Analia Roxana (2023)
The Carcinological Collection of the División Zoología Invertebrados, Museo de La Plata (FCNyM UNLP) currently contains 2446 lots, of which 124 represent type material. There is a total of 162 batches corresponding to parasitic crustaceans. Six orders are represented in the collection and recorded here: Arguloida, Cyclopoida, Siphonostomatoida, Harpacticoida, Isopoda, and the infraclass Rizocephala, belonging to four classes of the Suphylum Crustacea. The species names are listed in systematical order, and the type locality, collection number, current taxonomic status and original bibliographic reference are given. Host and site of infection are also provided.